Towards Al3+ Mobility in Crystalline Solids: Critical Review and Analysis. Issue 4 (4th July 2019) - Nestler, Tina; Fedotov, Stanislav; Leisegang, Tilmann; Meyer, Dirk C.
Abstract: Finding inorganic materials with significant Al ion mobility could push the development of alternative rechargeable batteries, as they could potentially serve as solid electrolytes or intercalation cathodes. While for single‐ and double‐charged ions numerous solid electrolytes are known, the situation is rather unclear and only sparingly researched for ions with a charge higher than two. To assist in the systematic analysis, compounds described in literature as solid electrolytes or intercalation materials for Al 3+, as well as some materials generally known for high mobilities for multivalent ions, are critically reviewed and analyzed by the bond‐valence energy landscape approach. For this purpose a thorough list of investigated cathode materials for rechargeable Al batteries is provided first. While it is demonstrated that solid electrolytes for Al 3+ cannot be unequivocally identified in literature yet, the analysis of the intercalation cathodes reveals promising structural motifs for comparatively fast Al diffusion, which can be used for the analysis, comparison and design of new promising materials. Furthermore, chances and limits of the bond‐valence energy analysis for high‐valent battery materials are exemplarily shown. Thus, this work aims at encouraging more theoretical and experimental work on Al battery materials and provides guidelines for doing so.